A Place at the Multicultural Table : the Development of an American Hinduism - Kurien, Prema A., 1963- (Book collections on Project MUSE., 2007)
Multiculturalism in the United States is commonly lauded as a positive social ideal celebrating the diversity of our nation. But, in reality, immigrants often feel pressured to create a singular formulation of their identity that does not reflect the diversity of cultures that exist in their homeland. Hindu Americans have faced this challenge over the last fifteen years, as the number of Indians that have immigrated to this country has more than doubled. In A Place at the Multicultural Table, Prema A. Kurien shows how various Hindu American organizationsreligious, cultural, and politicalare.